DAMPAK KEBIJAKAN SEKTOR RIIL TERHADAP STRUKTUR DAN KINERJA SEKTOR INDUSTRI INDONESIA, 1980-1994 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
Government intervention is one of classic agendas which has been discussed among economists. The Classic/New Classic economists believe that market would work more efficient in line with decreasing government interventions in economy. On the contrary, Keynesian economists argue that perfect competition market never happens in the world. They believe that government plays a central role to clear the market. Most developed countries have applied the Classic/New Classic's strategies in their economies. On the other hand, most of the less developed countries have used Keynesian strategies to increase their economic performances. Those differentces are influenced by the market system in each country. Economic globalization has indicated that the success of the development process of the nation will highly depend on the ability of the country to increase its competitive advantage. Increasing competitiveness is more important for a small country such as Indonesia. One of the main factors that can increase competitive advantages of the nation is the ability of the government to increase its economic efficiency. This article attempts to explore the impact of Indonesia's trade and industrial policy upon the structure, conduct and performance of hidonesian industrial sector. The aim of the study is to analyze Indonesian government intervention in the economy and the impact of the policy upon competitive advantages of industrial sector in Indonesia.